Rhodopsin gene expression regulated by the light dark cycle, light spectrum and light intensity in the dinoflagellate Prorocentrum - Shi, Xinguo; Li, Ling; Guo, Chentao; Lin, Xin; Li, Meizhen; Lin, Senjie (Frontiers in Microbiology, 2015)
The proton pump rhodopsin (PPR) is widely found in marine bacteria and archaea, where it functions to capture light energy and convert it to ATP. While found in several lineages of dinoflagellates, this gene has not been studied in Prorocentrales species and whether it functionally tunes to light spectra and intensities as in bacteria remains unclear. Here we identified and characterized this gene in the bloom-forming Prorocentrum donghaiense. It is a 7-helix transmembrane polypeptide containing conserved domains and critical amino acid residues of PPR. This gene is phylogenetically affiliated to the xanthorhodopsin clade, but seems to have a distinct evolutionary origin. Quantitative reverse transcription PCR (qRT-PCR) showed that in regular cultures, the transcript abundance of the gene exhibited a clear diel pattern, high abundance in the light period and low in the dark. The same diel pattern was observed for protein abundance with a Western blot using specific antiserum. The rhythm was dampened when the cultures were shifted to continuous dark or light condition, suggesting that this gene is not under circadian clock control. Rhodopsin transcript and protein abundances varied with light intensity, both being highest at a moderate illumination level. Furthermore, the expression of this gene responded to different light spectra, with slightly higher transcript abundance under green than blue light, and lowest abundance under red light. Transformed E. coli over-expressing this rhodopsin gene also exhibited an absorption maximum in the blue-green region with slightly higher absorption in the green. These rhodopsin-promoting light conditions are similar to the relatively turbid marine habitat where the species forms blooms, suggesting that this gene may function to compensate for the light-limited photosynthesis in the dim environment.